2018
DOI: 10.1002/ecs2.2311
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest temperature thresholds for gross primary productivity

Abstract: Tropical forests are hyper‐diverse and perform critical functions that regulate global climate, yet they are also threatened by rising temperatures. Canopy temperatures depart considerably from air temperatures, sometimes by as much as air temperatures are projected to increase by the end of this century; however, canopy temperatures are rarely measured or considered in climate change analyses. Our results from near‐continuous thermal imaging of a well‐studied tropical forest show that canopy temperatures reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 47 publications
4
80
1
1
Order By: Relevance
“…3). Pau et al (2018) also showed, using thermal imaging, that GPP was more strongly associated with canopy temperature than to T air or vapor pressure deficit. This response suggests that leaf photosynthesis is maintained at fairly cold leaf temperatures, even while respiration is suppressed.…”
Section: Application 2: Understanding How Thermal Variations Influencmentioning
confidence: 88%
See 1 more Smart Citation
“…3). Pau et al (2018) also showed, using thermal imaging, that GPP was more strongly associated with canopy temperature than to T air or vapor pressure deficit. This response suggests that leaf photosynthesis is maintained at fairly cold leaf temperatures, even while respiration is suppressed.…”
Section: Application 2: Understanding How Thermal Variations Influencmentioning
confidence: 88%
“…For example, Kim et al (2016) showed that leaf canopy temperature was a better predictor of variations in net ecosystem exchange. Pau et al (2018) also showed, using thermal imaging, that GPP was more strongly associated with canopy temperature than to T air or vapor pressure deficit. This study also used canopy thermal imaging to identify temperature-GPP dynamics, such as the temperature of peak GPP and the high-temperature threshold, beyond which GPP declined sharply.…”
Section: Application 2: Understanding How Thermal Variations Influencmentioning
confidence: 88%
“…Thermography has been used to estimate Esoil (Haghighi and Or, 2015;Nachshon et al, 2011;Shahraeeni and Or, 2010) and T from plant canopies (Jones, 1999;Jones et al, 2002), often in agricultural settings (Ishimwe et al, 2014;Vadivambal and Jayas, 2010). Researchers are increasingly using tower and UAV-mounted thermal cameras to measure the temperatures of different ecosystem 10 components at high temporal and spatial resolution (Hoffmann et al, 2016;Pau et al, 2018), which could revolutionize the measurement of T from plant canopies (Aubrecht et al, 2016) or even individual leaves in a field setting (Page et al, 2018).…”
Section: Advances In Thermal Imaging 30mentioning
confidence: 99%
“…Environmental conditions, including water availability and VPD, have also been examined in relation to satellite-based SIF in the Amazon and correlations were found between water stress conditions and increased variability in SIF measurements, yet specific relationships among VPD, T, and SIF remain uncertain in Amazon tropical forests and unexamined for other vegetation and biomes [22,35,83,84]. Measurements of canopy temperature (T can ) have been shown to differ from air temperature (T air ) in a tropical forest canopy by as much as 7 degrees Celsius and display better agreement with GPP [85].…”
Section: Introductionmentioning
confidence: 99%